Cyclometallated gold(iii) aryl-pyridine complexes as efficient catalysts for three-component synthesis of substituted oxazoles. Issue 12 (17th February 2015) - von Wachenfeldt, Henrik; Polukeev, Alexey V.; Loganathan, Nagarajan; Paulsen, Filip; Röse, Philipp; Garreau, Marion; Wendt, Ola F.; Strand, Daniel
Abstract : Cyclometallated gold(iii ) complexes efficiently catalyze the multicomponent reaction between imines, alkynes, and acyl chlorides to form trisubstituted oxazoles. Abstract : Cyclometallated aryl-pyridine gold(iii ) complexes are shown to be efficient catalysts for the multicomponent reaction between N -benzyl imines, alkynes, and acyl chlorides to form trisubstituted oxazoles. The reaction typically proceeds in good yields (up to over 80%) and short reaction times (∼15 minutes). The high stability of the investigated cyclometallated catalysts enables a retained efficiency for this reaction in terms of rate and yield using as little as 0.5 mol% catalyst, a reduction by an order of magnitude compared to previously used Au(iii )–salen complexes. An attractive feature of the present catalytic system is that active catalysts can be formed from simple pre-catalysts under the reaction conditions. Both cyclometallated and non-cyclometallated complexes were characterized in the solid state by single crystal X-ray diffraction.